Comparison of Power Relations Within Electronic and Face-to-Face Classroom Discussions: A Case Study - Laurel Jeris (Adult Education Research Conference, 2001)
Numerous aspects of design and delivery of online instruction are well researched but little exists on power relations of electronic versus face-to-face discussions and consequences for learning. This case study centers on the experiences of participants in a graduate course in human resource management. Implications for reconsidering prevailing views of adult education are discussed.